Evaluation of organo-mineral qualities of combusted compost floor litters in Achalla forest reserve on early growth responses of Dacryodes edulis H. J. Lam - Egwunatum, Anselm Enwelem; Emilimor, Patience Ndidi; Emma-Otum, Nneka Sophia; Doreen, Alukwe (International Journal of Agricultural Research, Innovation and Technology, 2023)
This study evaluated the potential of compost-combusted forest litters as alternative sources of ex-situ organo-mineral products to the direct use of controlled fire for enhanced soil nutrients in forest stands. Floor litters from six (6) delineated standing forest patches of Pterocarpus erinaceus, Gmelina arborea, Tectona grandis, Bambusa vulgaris, Ceiba pentandra and Mangifera indica were characterized for N, K, P, Ca and Mg; composted for 3, 6, 9 and 12 days and then uniformly combusted to produce organo-minerals for early growth response of Dacryodes edulis in a 6 x 4 split-plot factorial experiment. Analysis of variance was conducted for litter characteristics, calorific values, moisture, ash contents, and germination and growth variables of Dacryodes edulis while significant means were separated with DMRT (p ≥ 0.05). Results showed that Mangifera had the highest P (0.68%) and K (1.15%); Bamboo had the highest N (1.92%). Germination was 6>9>12> 3 days with Bamboo > Ceiba > Teak > Mangifera > Gmelina > Pterocarpus for 6 days organo-minerals, but the highest height (21.56 ± 6.77 cm) by Pterocarpus to implicate litters under microbe-thermal mediation as sustainable organo-mineral ex-situ products to combat incidence of forest fire for fertile forest soil. Thus, in-situ controlled fire in standing forests is no longer needed for nutrient-rich forest-agriculture. Int. J. Agril. Res. Innov. Tech. 13(1): 31-37, June 2023